TEXTURE AND MICROSTRUCTURE CHARACTERIZATION OF PASTES RECONSTITUTED FROM DRUM-DRIED FLAKES OF YAM (DIOSCOREA SPP.) - Amoin Georgette Konan; Judith Brunnschweiler-Beez; Jeannette Nuessli-Guth; Felix Escher; Beatrice Conde-Petit (European Scientific Journal, ESJ, 2014)
Drum-dried flakes were processed from two popular varieties of the tropical tuber crop yam species D. cayenensis-rotundata and reconstituted to dough like pastes, the most consumed form in Côte d’Ivoire. Pastes from flakes were compared to that prepared by a standardized laboratory procedure. The structure and texture of the pastes was characterized by instrumental and sensory analysis as well as microscopy. Large differences were found between the yam pastes from the two varieties in terms of changes in textural properties and structure upon the drum-drying processing. Reconstituted paste from the variety Assawa was perceived by the sensory panel as more springy and chewy whereas that of Kponan was less extensible and sticky. Although, no significant difference was found in mechanical properties, in terms of firmness, elasticity and adhesion of pastes. Light micrographs revealed that the variety Kponan was less susceptible to cell rupturing.